Consumer Research Needs from the Food and Drug Administration on Front-of-Package Nutritional Labeling. (April 2014) - Andrews, J. Craig; Lin, Chung-Tung Jordan; Levy, Alan S.; Lo, Serena
Americans have increasingly busy lifestyles and desire quick and nutritious food choices. To provide consumers with at-a-glance nutrition information, many food manufacturers have introduced front-of-package (FOP) nutritional labeling systems. The purpose of this review is to reach out to the marketing and public policy discipline by identifying research needs on FOP systems not only to aid decision making for federal agencies, but also to help advance research on this important topic. We describe the many FOP systems, the FDA's regulatory background and approach to FOP systems, recent experimental research and gaps in knowledge, and research needs on FOP nutrition labeling.